Chimeric Antigen Receptor-Modified T Cell Immunotherapy for Relapsed and Refractory Adult Burkitt Lymphoma - Wu, Jiaying; Cao, Yang; Zhang, Qi; Liu, Wanying; Zhou, Xiaoxi; Ming, Xi; Meng, Fankai; Zhang, Yicheng; Li, Chunrui; Huang, Liang; Wei, Jia; Zheng, Miao; et al. (Frontiers in Immunology, 2022)
Patients with Burkitt lymphoma who are refractory to initial therapy or who relapse after undergoing intensive chemotherapy and autologous stem cell transplantation (ASCT) usually have a poor prognosis. While there has been considerable progress in the use of chimeric antigen receptor-modified (CAR) T cell immunotherapy for the treatment of relapsed and refractory (r/r) malignancies, explicit data on adult patients with r/r Burkitt lymphoma are limited. We conducted two single-arm clinical trials to evaluate the clinical efficacy and toxicity of CD19/CD22 CAR T cell immunotherapy both alone (trial A) and in combination with ASCT (trial B) in adult patients with r/r Burkitt lymphoma. In total, 28 adult patients with r/r Burkitt lymphoma were enrolled [trial A (n = 15) and trial B (n = 13)]. The median doses of CD22 and CD19 CAR T cell infusions were 4.1 × 106/kg and 4.0 × 106/kg, respectively. Subsequently, after CAR T cell infusion, overall and complete responses were observed in 19 (67.9%) and 16 (57.1%) patients, respectively. The cumulative incidence rates of grade 2–4 cytokine release syndrome and immune effector cell-associated neurotoxicity syndrome were 39.3% (11/28) and 10.7% (3/28), respectively. After a median follow-up duration of 12.5 months, 16 patients (5 in trial A and 11 in trial B) survived. Both the estimated 1-year progression-free and overall survival rates were 55.6%. Our preliminary results indicated that salvage therapy with CD19/CD22 CAR T cell infusion alone and that in combination with ASCT are effective in treating some adult patients with r/r Burkitt lymphoma.